Opportunities for probiotics and polyunsaturated fatty acids to improve metabolic health of overweight pregnant women - K. Mokkala; H. Röytiö; U. Ekblad; K. Laitinen (My University, 2022)
Overweight during pregnancy predisposes both the mother and foetus to health complications. Maternal complications include gestational diabetes, obstetric problems and type 2 diabetes later in life. Complications for the offspring are not only restricted to the foetal period or birth, such as prematurity and foetal macrosomia, but may also have long-term metabolic health implications through the mechanism of early nutrition programming. One of the key metabolic components characterising overweight in the non-pregnant state is low-grade inflammation manifested by elevated levels of circulatory pro-inflammatory cytokines. In pregnancy, in addition to adipose tissue and placenta, inflammatory response may originate from the gut. The extent to which overweight induces metabolic maladaptation during pregnancy and further compromises maternal and child health is currently poorly understood. In this review, we evaluate recent scientific literature and describe the suggested links between overweight, gut and low-grade inflammation associated metabolic disorders. We focus on overweight pregnant women and gestational diabetes, and discuss how specific dietary factors, probiotics and long-chain polyunsaturated fatty acids (fish oil), might confer health benefits in combatting against metabolic risk factors.